ANALISIS STRATEGI PEMANFAATAN KITAB SUCI DALAM PENANAMAN KREATIVITAS ANAK BINA IMAN ANAK KATOLIK (BIAK): SYSTEMATIC LITERATURE REVIEW - Floriana Lali Basa (SOSCIED, 2026)
This study aims to analyze various strategies for utilizing the Holy Scriptures to foster creativity among children in Catholic Children's Faith Formation (BIAK) and the Pontifical Society of Missionary Childhood (SEKAMI), focusing specifically on the process of preparing catechetical materials by facilitators. A Systematic Literature Review (SLR) method, structured according to PRISMA guidelines, was employed. A comprehensive literature search was conducted by screening scholarly articles from reputable national and international databases—including Google Scholar, Garuda (Garba Rujukan Digital), SINTA, and Scopus—covering the period from 2016 to 2026. The review results indicate that creativity among Catholic children can be effectively stimulated through three adaptive strategies for preparing Scripture-based teaching materials: (1) the use of three-dimensional and tactile-sensory media (such as pop-up books and Montessori-style props); (2) contextualized conventional narrative visualization; and (3) the digitalization and gamification of catechesis based on User-Centered Design (UCD) principles. The study offers a methodological roadmap for BIAK facilitators to prepare catechetical materials that strike a balance between doctrinal-theological content and a creative, engaging, and child-oriented psycho-pedagogical approach.